2017
DOI: 10.1542/peds.2016-3640
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Insurance and Transfer of Injured Children From Emergency Departments

Abstract: Injured pediatric patients presenting to nondesignated trauma centers are slightly more likely to be transferred than admitted when the ED treats a higher proportion of Medicaid patients. In this study, ongoing concerns about inequities in the delivery of care among hospitals treating high proportions of children with Medicaid are reinforced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Other studies have demonstrated that private insurance and lack of insurance have been associated with undertriage 16 17. We add nuance with our analyses in considering private HMO and private non-HMO insurances separately.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that private insurance and lack of insurance have been associated with undertriage 16 17. We add nuance with our analyses in considering private HMO and private non-HMO insurances separately.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of our patient population were transferred from an outside facility and accounted for most of the injuries seen, admissions, and discharges. One prior study found that EDs with a larger proportion of Medicaid patients had a higher odds of transferring patients with Medicaid over private payer (Huang et al, 2017). Of the remaining 30% of children in the GCTR database that were not transferred to CHOA for care, the majority received care at either an adult level 1 or level 2 trauma center.…”
Section: Discussionmentioning
confidence: 99%
“…(Delgado et al, 2014 ) In a similarly designed pediatric study including more than 9000 traumatically injured children, those with public insurance had a higher odds of transfer to a dedicated trauma center from a referral hospital when compared to children with private insurance (odds ratio [OR]: 1.3; 95% CI: 1.0–1.5). (Huang et al, 2017 ) These studies suggest that non-clinical factors, including attempts to minimize revenue losses from treating underinsured patients, may influence triage decisions. (Delgado et al, 2014 ; Huang et al, 2017 )…”
Section: Discussionmentioning
confidence: 99%
“…(Huang et al, 2017 ) These studies suggest that non-clinical factors, including attempts to minimize revenue losses from treating underinsured patients, may influence triage decisions. (Delgado et al, 2014 ; Huang et al, 2017 )…”
Section: Discussionmentioning
confidence: 99%